PENERAPAN TUGAS PENGAWASAN SUPERVISOR DI DEPARTEMEN HOUSEKEEPING HOTEL PANGERAN BEACH PADANG - Fernando, Ricky Bayuandry; Yuliana, Yuliana; Suyuthie, Hijiriyantomi (Journal of Home Economics and Tourism, 2016)
This research aimed to describe the application of supervisor’s supervisory tasks of the housekeeping department at Pangeran Beach Hotel Padang, evaluated from four indicators which are: monitoring of the human resources, the use of materials, work equipment and work systems. The research uses a qualitative descriptive survey method. Data was collected by using observation, interviews, and documentation. The results showed that the application of supervisor’s supervisory tasks of the housekeeping department at Pangeran Beach Hotel Padang is fair, although there are some indicators that supervision can not be implemented properly by the supervisor. Such as oversight of the mental condition of the employees, the use of materials, procurement and storage of the work equipment, the implementation of the Standard Operating Procedure. As for the performance assessment, employee recruitment and employee career system is not implemented by supervisors because it is not the task of the housekeeping supervisor at Pangeran Beach Hotel Padang.   Keyword: Controlling, Supervisor, Housekeeping